2008
DOI: 10.1007/s11418-008-0235-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sesbania grandiflora for antiurolithiatic and antioxidant properties

Abstract: In the indigenous system of medicine in India, the plant Sesbania grandiflora is claimed to be useful for various ailments, and one such use is for the treatment of renal calculi. The major purpose of this study is to investigate the potential of S. grandiflora in the treatment of renal calculi. The leaf juice of S. grandiflora was evaluated for median lethal dose, gross behavioral changes, antiurolithiatic and antioxidant activities. The antiurolithiatic activity was evaluated by a calculi-producing diet mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…There was no any behaviourl changes in rats except excessive urination. [54] l) Immunomodulatory activity…”
Section: D) Antidiabetic Propertymentioning
confidence: 99%
“…There was no any behaviourl changes in rats except excessive urination. [54] l) Immunomodulatory activity…”
Section: D) Antidiabetic Propertymentioning
confidence: 99%
“…It has been reported that the oral administration of leaves extract even at the maximum single dose of 2000 mg/kg body weight was found to be safe, since no mortality 41 .…”
Section: Table 9: Effect Of Sesbania Grandiflora Extract On the Activmentioning
confidence: 99%
“…Sesbania grandiflora possess hepatoprotective 8 , anticancer activity 9 . For congenital bronchitis or cold in babies, leaf juice mixed with honey is often recommended 10 (Nadkarni, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…S. grandiflora leaves used for the treatment of nervous system diseases such as anxiety and convulsion (Kasture et al 2002). Besides, it has antifertility, anti-inflammatory, analgesic, antipyretic, antiurolithiatic, anticancer, antioxidant, antibacterial, and cytoprotective activity (Shrivastav and Janin 1993;Tamboli 1996Tamboli , 2000Doddola et al 2008;Sreelatha et al 2011;Kumaravel et al 2011;Zarena et al 2014). Our earlier experiments reported some protective effects of S.grandiflora on cigarette smokeexposed rats (Ramesh et al 2007(Ramesh et al , 2010(Ramesh et al , 2014.…”
Section: Introductionmentioning
confidence: 99%